Spatial Memory Deficits in a Virtual Reality Eight-Arm Radial Maze in Schizophrenia - Spieker, Elena A. (2011)
Learning and memory impairments are present in schizophrenia (SZ) throughout the illness course and predict psychosocial function. Abnormalities in prefrontal and hippocampal function are thought to contribute to SZ deficits. The radial arm maze (RAM) is a test of spatial learning and memory in rodents that relies on intact prefrontal and hippocampal function. The goal of the present study was to investigate spatial learning in SZ using a virtual RAM. Thirty-three subjects with SZ and thirty-nine healthy controls (HC) performed ten trials of a virtual RAM task. Subjects attempted to learn to retrieve four rewards each located in separate arms. As expected, subjects with SZ used more time and traveled more distance to retrieve rewards, made more reference (RM) and working memory (WM) errors, and retrieved fewer rewards than HC. It is important to note that the SZ group did learn but did not reach the level of HC. Whereas RM errors decreased across trials in the SZ group, WM errors did not. There were no significant relationships between psychiatric symptom severity and maze performance. To our knowledge, use of a virtual 8-arm radial maze task in SZ to assess spatial learning is novel. Impaired virtual RAM performance in SZ is consistent with studies that examined RAM performance in animal models of SZ. Results provide further support for compromised prefrontal and hippocampal function underlying WM and RM deficits in SZ. The virtual RAM task could help bridge preclinical and clinical research for testing novel drug treatments of SZ.